2016
DOI: 10.1021/acsnano.5b07511
|View full text |Cite
|
Sign up to set email alerts
|

Laser Writing Block Copolymer Self-Assembly on Graphene Light-Absorbing Layer

Abstract: Recent advance of high-power laser processing allows for rapid, continuous, area-selective material fabrication, typically represented by laser crystallization of silicon or oxides for display applications. Two-dimensional materials such as graphene exhibit remarkable physical properties and are under intensive development for the manufacture of flexible devices. Here we demonstrate an area-selective ultrafast nanofabrication method using low intensity infrared or visible laser irradiation to direct the self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 67 publications
0
99
0
1
Order By: Relevance
“…In this respect, dots and stripes, two basic elements of lithographic patterns, can be obtained from BCP thin films featuring cylinders and lamellae perpendicularly oriented with respect to the substrate . Thus, the control of the domain orientation represents an essential key for the technological application of these materials in lithographic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, dots and stripes, two basic elements of lithographic patterns, can be obtained from BCP thin films featuring cylinders and lamellae perpendicularly oriented with respect to the substrate . Thus, the control of the domain orientation represents an essential key for the technological application of these materials in lithographic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al demonstrated the robust and noteworthy way to triboelectric generators with nanoscale tunable surface using very controllable nanostructures via block copolymer (BCP) selfassembly processes [77]. The BCP nanopatterning and nanolithography is a very powerful approach for bottomup nanofabrication processes to achieve various device applications [93,94]. As shown in Figure 4(a), various silica surface nanopatterns including nanodots, nanogrates, and nanomeshes on the large-area device were established according to the experimental conditions by the self-assembly of polystyrene-blockpolydimethylsiloxane (PS-b-PDMS) BCP.…”
Section: Surface Texturing and Patterningmentioning
confidence: 99%
“…To implement a high‐performance operational PCM, a variety of factors should be considered such as scaling methods, cell design optimization, thermal engineering, material exploration, and selection device integration . Park et al proposed a strategy for reducing the switching power of the PCM by incorporating PS‐ b ‐PDMS BCP‐based nanostructured SiO x between the GST chalcogenide material and the TiN heater, as illustrated in Figure a . The phase transition volume of the GST was shrunk by operation current concentration, resulting in a significant reduction of the writing power by 1/20 when the fill factor increased from 9.1% to 63.6%, as shown in Figure b.…”
Section: Inorganic Phase‐change Memoriesmentioning
confidence: 99%